THE INFLUENCE OF BRAND AMBAS THE INFLUENCE OF BRAND AMBASSADOR, BRAND IMAGE AND ADVERTISING ON PURCHASING DECISIONS AT SHOPEE: - - , Feronika Verawati Samosir; Rutman Lumbantoruan; Netty Laura (Universitas Kristen Indonesia, 2024)
This research is quantitative research used to see the influence of brand ambassadors, brand image and advertising on purchasing decisions at Shopee in the people of Puri Kembangan Selatan Subdistrict. Determining as many samples as determined in the Taro Yamane formula where the population is known. The research results at the significant level for (1) variable (X1) are 0.275 > 0.05 with a calculated t value < t table of (1.107 < 1.990), meaning that Brand Ambassador is partially positive but not significant in purchasing decisions. (2) The significant level of Brand image (X2) is 0.000 < 0.05 with a calculated t value > t table of (6.213> 1.990) which means that it partially has a positive and significant effect on purchasing decisions. (3) The significant level of advertising is 0.000 < 0.05 with a calculated t value > t table of (11.624 > 1.990). The results of the simultaneous test show that the calculated f value is 337.469 > 2.72 and the significance is 0.000 < 0.05, which means that X1, The researcher's suggestions for Shopee E-commerce where the Brand Ambassador variable section has the lowest score, so Shopee should be able to increase the Brand Ambassador value by appointing Brand Ambassadors who are very popular so that they can attract more consumer attention, especially to Shopee E-commerce in the future. Keywords: Brand Ambassador, Brand image, Advertising, Purchase Decision